Apakah Keputusan Pembelian Konsumen Akan Meningkat Karena eWOM dan Gaya Hidup? - Handiyani, Ni Luh; Benni Kusyana, Dewa Nyoman (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2022)
Purchase decisions are influenced by several factors, including electronic word of mouth and lifestyle. This study was conducted with the aim of knowing the effect of electronic word of mouth and lifestyle on online purchasing decisions on Instagram social media. This research was conducted in Gianyar Regency on people who have Instagram social media accounts and have shopped through Instagram with an unknown amount. Determination of the number of samples is carried out by considering five times the number of indicators, namely as many as 29 indicators so that the sample is set at 145 respondents with purposive sampling technique. The questionnaire that has been answered by the respondents based on the Likert Scale was then tested for validity and reliability with SPSS software and continued with classical assumption testing and multiple linear regression analysis to answer the hypothesis. The results showed that electronic word of mouth and lifestyle had a positive and significant effect on purchasing decisions.